An Investigation of Pre-Service Elementary and Secondary Mathematics Teachers' Number Sense (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2016)
The aim of the study is to investigate primary and secondary pre-service mathematics teachers’ number sense. A total of 464 mathematics teachers are participated in the study. To measure the number sense performances of the pre-service mathematics teachers with a Number Sense Test, including 31 multiple-choice questions, was developed by the researchers. Number Sense Test is a two-tailed test which includes the number sense questions and their possible solution strategies. Students’ answers of Number Sense Test were analyzed to find the number sense points in terms of two aspects; one of them were correctness (True or False) and the second one was solving strategies (Number sense strategy or Rule based strategy) of pre-service teachers. According to the data analysis, mathematics teachers had low performance and they preferred to use rule based strategies rather than number sense strategies. Although there is a positive correlation between Number Sense Test performance and using number sense skills, there is no significant difference between male and female pre-service teachers and their departments at using number sense.